A Closer Examination of White Student Enrollment at HBCUs. Issue 170 (June 2015) - Shorette, C. Rob; Arroyo, Andrew T.
Abstract : This chapter closely examines trends in White student enrollment at 4‐year HBCUs between 1987 and 2012 and discusses the implications of those trends for policy, practice, and future research.